EFFECTIVE SOLUTION TO PROBLEMS IN MENTAL DEVELOPMENTTHE INDEPENDENCE OF STUDENTS IN A FOREIGN LANGUAGE - Artikova Mavjuda Maksudovna (International Engineering Journal For Research & Development, 2020)
These article deals with pedagogical process, which help students to enrich independently effective methods in the system of teaching process in order to learn the materials of the lessons process effectively.